2010
DOI: 10.1021/pr900605q
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Screening for Possible Effector Molecules Secreted by the Obligate Intracellular Pathogen Coxiella burnetii

Abstract: Coxiella burnetii is a Gram-negative, gamma-proteobacteria with nearly worldwide distribution, and it is the pathogenic agent of Q-fever in man. It is an obligate intracellular parasite that is highly adapted to reside within the eukaryotic phagolysosome. In fact, it is the only known intracellular bacterium that manages to survive and replicate within a fully formed, acidic phagolysosome. C. burnetti possesses a functional Type 4 Secretion System (T4SS), similar to the Dot/Icm system of Legionella pneumophila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…Additionally, 150 proteins not reported in previous proteomic studies of C. burnetii [40][41][42][43][44][45][46] were identified in this study (Supplemental Table 3). Among these are a number of proteins potentially associated with pathogenicity and virulence.…”
Section: 4mentioning
confidence: 67%
See 2 more Smart Citations
“…Additionally, 150 proteins not reported in previous proteomic studies of C. burnetii [40][41][42][43][44][45][46] were identified in this study (Supplemental Table 3). Among these are a number of proteins potentially associated with pathogenicity and virulence.…”
Section: 4mentioning
confidence: 67%
“…The last, (Q83B72) was not detected in any previous study of C. burnetii. The DotD protein is an essential component of the C. burnetii type IV secretion system, and is mechanistically related to the Legionella Dot/Icm apparatus [45,[79][80][81]. Recently it has been suggested that the Dot/Icmrelated secretion system has an important role during phagosome establishment [80].…”
Section: 4mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, CpeD and potentially other Dot/Icm substrates may influence ER function. It should be noted that CpeD was also identified in a proteomic screen of C. burnetii secreted proteins (54).…”
Section: Discussionmentioning
confidence: 99%
“…The use of L. pneumophila as a surrogate host led to the identification of 32 proteins that were translocated into host cells in a Dot/Icm-dependent manner. Interestingly, two of the identified Dot/Icm substrates (CBU1314 and CBU1823) are suggested to localize in the cytoplasm of C. burnetii infected Vero cells (by mass spectrometry) (35). Although the biological significance of the interaction between protein substrates and components of the transport system is largely undefined, such interactions have been very useful in identifying novel substrates (5,18,36).…”
Section: Discussionmentioning
confidence: 99%